2019
DOI: 10.1002/joc.6371
|View full text |Cite
|
Sign up to set email alerts
|

The implication of spatial interpolated climate data on biophysical modelling in agricultural systems

Abstract: Spatial modelling of agricultural production has been more frequently analysed to assist with regional and long‐term planning. Typically, point‐scale crop models are used to construct these analyses with researchers using various sources of input data, including observed and interpolated gridded climate data. Understanding the implication of data choice on production estimates is crucial to appreciate the consequences of selecting methodological approaches for agricultural model outputs. In this study, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Additionally, trends in more frequent and less intense rainfall can impact winter crop growth. For example, storage of sub‐soil moisture over summer may be reduced as frequent, ineffective small rainfall events were lost through evaporation rather than filling the soil profile for subsequent crop use (Liu et al ., 2019; Liu et al ., 2020). In southern NSW and Victoria, winter cropping was the dominant agricultural system but with reduced growing season rainfall and less soil moisture storage these systems will be challenged to maintain future productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, trends in more frequent and less intense rainfall can impact winter crop growth. For example, storage of sub‐soil moisture over summer may be reduced as frequent, ineffective small rainfall events were lost through evaporation rather than filling the soil profile for subsequent crop use (Liu et al ., 2019; Liu et al ., 2020). In southern NSW and Victoria, winter cropping was the dominant agricultural system but with reduced growing season rainfall and less soil moisture storage these systems will be challenged to maintain future productivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, using station data instead of gridded data was a deliberate choice as interpolation typically introduced additional uncertainty in rainfall. The gridded data can result in larger rainfall frequency and smaller rainfall intensity when compared with station data (Liu et al ., 2020), which would also have implications for examination of rainfall trends. The high‐quality stations with a high proportion of observed data minimized the data‐source bias interfering to the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Complexifying the issue, there are now several available data sources for meteorological forcing data 4,5 . Recent work 6,7 has shown that impact model results are influenced by the choice of forcing data. Providing several relevant forcing datasets should therefore be considered important to better understand how uncertainties propagate in the water resources management chain.…”
Section: Background and Summarymentioning
confidence: 99%
“…A key reason for using the data from 27 GCMs was to better quantify the spatiotemporal distribution of and variability in precipitation during the growing season. We downscaled the GCM datasets using the NASA/POWER gridded historical weather database 64 . However, previous work has shown that interpolated gridded data tends to be conducive to producing rainfall events that are smaller in quantum but more frequent, which can lead to lower surface runoff and higher soil evaporation 64 .…”
Section: Resultsmentioning
confidence: 99%